Factors influencing family care by immigrant women in Spain: a qualitative study - Casado Mejía, Rosa; Ruiz Arias, Esperanza (Investigación y Educación en Enfermería, 2016)
Objective. To identify and understand factors that influence the relationships in the environment of family care provided by live-in immigrant caregivers. Methods. Interpretive qualitative study from a phenomenological perspective, using in-depth interviews, discussion groups and participant observation. The observation unit was the Sevillian families (Spain) with elderly dependents and a live-in female immigrant caregiver. Analysis units considered were health, care, dependence, gender, ethnicity and social class. Categories were analysed using QSR-NUD*ISTVivo9. After saturation, we triangulated between researchers, disciplines, sources and techniques to validate the results. Results. Factors of cultural discovery or clash were: language, religion, food, concept of space and time, caregiver’s name and the attitudes held by both the hiring family, related to its social class, and by caregivers. Conclusion. Interpersonal relationships are the most important factor: an egalitarian relationship based on good treatment is beneficial to all involved. Knowing these codes will improve the quality of professional care in the family. How to cite this article: Casado-Mejía R, Ruiz-Arias E. Factors influencing family care by immigrant women in Spain: a qualitative study. Invest. Educ. Enferm. 2016; 34(3): 551-563.